Impact of Educational Interventions on Materiovigilance Awareness among Pharmacy Students: A Cross-Sectional Study - Gore, Akshata; Sayed, Arfa Anwar; Sail, Shamita Shyam; Khan, Ramish; Swamy, Agadi Hiremath Viswanatha; Nyamagoud, Sanatkumar Bharmu (International Journal of Pharmaceutical Investigation, 2025)
Background Medical devices are used vitally in the healthcare system. Since India is a developing country, it didn’t have a valid outline to screen and notice the adverse events occurred using medical devices. Hence, materiovigilance supports the administrative experts in decision-making, for example, working with the public as well as globally on MDAEs (Medical device adverse events) reporting and their examinations to prevent any up-coming adverse events related to medical device utilization in the future. As it helps healthcare professionals to analyse and manage sickness or injuries. Materials and Methods This was a cross-sectional, self-designed questionnaire-based study conducted over a duration of six months, with participants involved undergraduates (n=410) and postgraduates (n=135). 15-item questionnaire assessed KAP, that administered with an educational intervention. Data was analysed using IBM SPSS 27.0, and internal consistency was verified with Cronbach’s alpha. Results Total of 545 participants responded, where intervention was highly effective in knowledge (97.01%) and perception (79.10%) among postgraduate, similar scores observed in attitude of UG (74.57%) and PG (72.38%). Conclusion This study highlights notable improvements in Knowledge, Attitude, and Perception (KAP) related to materiovigilance among pharmacy students in KAP domains, where statistical analysis confirmed with postgraduates generally achieving higher post-test scores, whereas undergraduates indicated higher interventions as well. Postgraduates displayed more progress particularly in Good Knowledge that rose from 32.8% to 97.01%. These results emphasized the value of educational interventions in raising materiovigilance awareness for incorporating such programs into pharmacy curricula to encourage the reporting of MDAEs.
Keywords: Interventions; Materiovigilance; Participants; Postgraduates; Undergraduates